2021
DOI: 10.22516/25007440.649
|View full text |Cite
|
Sign up to set email alerts
|

Tumor de estroma gastrointestinal extraintestinal gigante: reporte de un caso y revisión de bibliografía

Abstract: Los tumores del estroma gastrointestinal (GIST) son tumores infrecuentes del tracto digestivo. Sus localizaciones más frecuentes son el estómago, intestino delgado, colon y recto; su aparición en otros lugares fuera del trato gastrointestinal como el mesenterio, epiplón o retroperitoneo es infrecuente. La tomografía axial computarizada (TAC) y la resonancia magnética (RM) son los estudios de imágenes de primera elección. La recesión quirúrgica es el estándar de oro para los tumores localizados y en los tumores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…GIST patients develop variable and nonspecific clinical presentation, according to size and location of the tumor, but are often asymptomatic and end up being diagnosed incidentally 2,3,14 as in the present case. The most frequent symptoms are anemia, weight loss, gastrointestinal bleeding, abdominal pain, symptoms related to mass effect, and may also present intestinal obstruction, perforation, and peritonitis 14 .…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…GIST patients develop variable and nonspecific clinical presentation, according to size and location of the tumor, but are often asymptomatic and end up being diagnosed incidentally 2,3,14 as in the present case. The most frequent symptoms are anemia, weight loss, gastrointestinal bleeding, abdominal pain, symptoms related to mass effect, and may also present intestinal obstruction, perforation, and peritonitis 14 .…”
Section: Discussionmentioning
confidence: 60%
“…On CT, these tumors are encapsulated and have heterogeneous contrast uptake due to the presence of areas of necrosis 8 . It is also possible to identify areas of hemorrhage, intralesional calcification, and metastatic disease 4,14 . Metastases are not rare and the most affected sites include the liver and peritoneum 2,3,8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, in gastrointestinal cancer, increased CRP is associated with progressive disease, advanced stages of metastatic cancer, and poor survival [ 738 ]. Some case reports show notably elevated CRP values (>100 mg/L) during the diagnosis of extraintestinal Gastrointestinal Stromal Tumor (GIST), and a study indicated that CRP was higher while taking into account the location of the lower digestive tract, larger tumor size, and the higher mitotic index of the specific GIST [ 819 , 820 , 821 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%